Online Fraud Types and Open-Source Online Fraud Prevention Tools– An Analysis - Vijayarani, S; Janani, R (International Journal of Computer Sciences and Engineering, 2022)
The evolution of the world economy has been very high with the proliferation of new technology and universal communication super highways. Nonetheless, one of the unintended consequences of online or the internet is its use for illegal activities. Increasing social crime has become a global problem, and the activity of international criminal organizations has been steeply increased. Online fraudulent usually denotes to any form of fraud mechanism that uses the internet's one or more components, such as emails, websites, web portals, etc. Nowadays, many tools are available to prevent the users from online fraudulent. The main aim of this paper to discuss the types of online fraud and tools to prevent those fraud activities.